Determination of the external potential of education in the era of the industrial revolution 4.0 and society 5.0 in Indonesia - Anatun Nisa Mun'amah (Green Publisher, 2023)
Determination of the external potential of education in the era of the industrial revolution 4.0 and society 5.0 in Indonesia is a scientific article in the literature study within the scope of the management of education. This study aims to provide an analysis of the determination of the external potential of education in the era of the industrial revolution 4.0 and society 5.0. obtained from the results of a literature review or literature study by comparing various written sources such as articles, journals and books that are relevant to the studies in this study. The results of this study provide an analysis that the presence of the industrial revolution 4.0 and 5.0 made a major contribution to Indonesian education. by creating change and preparing superior and innovative graduates with pre-prepared skills through revitalizing the education system by strengthening the elements in it, both quality human resources, infrastructure that supports digitalization, and curriculum alignment that is integrated to five basic values, namely resilience, adaptability, integrity, competence, and continuous improvement.